Effects of an Abbreviated and Adapted PEERS® Curriculum as Part of a College Transition Program for Young Adults on the Autism Spectrum. (May 2023) - Howorth, Sarah K.; Rooks-Ellis, Deborah L.; Cobo-Lewis, Alan; Taylor, Joshua; Moody, Christine T.
College students on the autism spectrum report the following support needs: interpersonal skills and coping with unexpected change. The purpose of this pilot study was to investigate the effects of an interpersonal skills seminar using elements of the PEERS® curriculum on the acquisition of conversational behaviors by three young adults on the autism spectrum who were attending a summer college transition program designed to help prepare and familiarize individuals with college living. A multiple probe across behaviors design was used. According to visual analysis, a functional relation was not established between participation and acquisition of foundational conversational skills. Our findings provide a model for how state vocational rehabilitation agencies and institutes of higher education can collaborate to provide effective support for college students with autism spectrum disorder.